Optimalisasi Sistem Social Media Marketing untuk Membangun Awareness dengan Membuat Konten Online - Rafi, Raihanda; fajriana, M. Risvan; Jayawardhana, Irman; Susilo, Radityo; Miradiarsyah, Junas (Stupa, 2021)
The research explained about a sport event called Event Basket Pro that has been established since 2003, Event Basket Pro is one of professional basketball league in Indonesia and runs for approximately 8 months every season. Improvements are needed to make this event sustain, despite the fact that this event has operated for more than 15 years. Based on the research that was conducted using Soft System Methodology, it was found that Event Basket Pro having difficulties to create relevant digital marketing content related to their marketing target. The author suggested optimalizaton the system of social media marketing. In order to achieve it, according to the recommendation of conceptual model, every stakeholders had to play their role in planning, implementing and evaluation.